Rare Case Report of Pilomatrical Carcinosarcoma in a Pediatric Patient. (March 2020) - Gates, Gregory A.; Nguyen, Johnny; Binder, Scott W.
Abstract : Abstract: We present a case report of the exceptionally rare pilomatrical carcinosarcoma in an even rarer pediatric age group, a 9-year-old female patient. The tumor showed biphasic pilomatrical carcinoma and malignant sarcomatous transformation. To date, the patient is healing well without signs of recurrence. Although limited clinical follow-up is available due to the recent diagnosis, this case may provide a rare look at the clinical outcome of this very rare tumor.